Morphological spectrum of leukemic mantle cell lymphoma - Khaliqur Rahman; P G Subramanian; Pratibha Amare Kadam; Vijaya Gadage; Komal Galani; Neha Mittal; Sitaram Ghogale; Yajamanam Badrinath; Rashida Ansari; Shilpa Kushte; Reena Nair; Manju Sengar; et al. (Wolters Kluwer Medknow Publications, 2012)
Background: Leukemic involvement in mantle cell lymphoma (MCL) is common, and can be secondary to nodal or extranodal disease or can be de-novo. There is paucity of literature that describes the morphological spectrum. Aim: This study was aimed at studying the morphological spectrum of leukemic MCL and to correlate the morphology with other features. Materials and Methods: Twenty six such cases diagnosed over a period of four years were studied. Peripheral blood and bone marrow aspiration smears stained with Wrights stain were examined by three hematopathologists. Immunophenotyping was done using multicolor flow cytometry. Fluorescence in situ hybridization (FISH) done in 12 cases showed t(11;14)(q13:q32). Results: Six cases had de-novo leukemic involvement; while 20 cases had secondary involvement. Morphologically, the cells were small (less than twice the size of red blood cell) or large. Small cell morphology in turn showed irregular nuclear border (n=13) or round nuclear contour (n=6). Large cells had blastic morphology (n=5) or had central prominent nucleoli resembling prolymhphocytes (n=2). Twenty cases showed characteristic immunophenotype of CD5+/CD19+/CD20+/FMC7+/CD10-/CD23- and light chain restrictions. Three cases expressed CD23 and two cases were negative for FMC7. Five out of 12 cases, where FISH was done, showed cytogenetic abnormalities in addition to t(11;14)(q13;q32). Conclusion: Morphological spectrum of leukemic MCL ranges from small cells resembling chronic lymphocytic leukemia (CLL) or follicular lymphoma (FL) to large cell mimicking prolymphocytic leukemia (PLL) or acute leukemia. Large cell morphology was associated with more frequent additional cytogenetic abnormality as well as a poorer outcome.